Thai heritage, world heritage. ([Bangkok] Office of Archaeological and National Museum III Phanakorn Sri Ayutthaya Fine Arts Department, Ministry of Education, 2000)
With reference to the sites in Thailand.
"Further reading": p. 35.
Keywords: Natural areas -- Thailand; World Heritage areas -- Thailand; Cultural property -- Protection -- Thailand; Historic sites -- Conservation and restoration -- Thailand; Thailand -- Antiquities -- Collection and preservation